From participation to public value: transforming village fund governance through community engagement - RM. Mahendradi; Endang Larasati; Sri Suwitri; Tri Yuniningsih; Augustin Rina Herawati; Dyah Lituhayu (Indonesian Institute For Counseling, Education and Therapy, 2026)
Village Fund governance in Indonesia has largely been approached as an administrative and fiscal mechanism, overlooking community participation's potential to generate public value. Citizen involvement thus remains procedural, limiting social legitimacy, trust, and development outcomes. This study addresses the need to transform Village Fund governance through substantive participation as a foundation for public value creation. Substantive participation is operationally defined as community involvement across the entire Village Fund cycle (planning, implementation, monitoring, evaluation) characterized by deliberative spaces, information access, feedback mechanisms, and tangible influence on final decisions—beyond mere attendance in formal forums. The objective is to analyze how substantive participation and institutional collaboration contribute to governance transformation and public value formation in rural contexts. A descriptive qualitative approach with a multiple case study design was conducted in three villages in Magelang Regency (high, moderate, and low participation). Data were collected through interviews, participatory observation, and document analysis. Thematic analysis compared patterns across villages. Findings reveal that substantive participation and institutional collaboration are key determinants of social legitimacy, operational capacity, and public value outcomes. Causal mechanisms are non-linear: in the high-participation village, a public value forum facilitated by a youth organization enabled residents to propose and monitor an irrigation project. Residents’ trust in the village head increased from 52% to 89% within one year, and fund irregularities declined due to community-based monitoring (real-time information boards and invoice verification). Conversely, the low-participation village exhibited low moral legitimacy and 23% budget leakage.